Integrating Character Education and Social Studies in Elementary School: Prospective Professional Teachers’ Experiences - Antara, I Gede Wahyu Suwela; Swadnyana, Ida Bagus Yoga; Yudiana, Kadek; Arini, Ni Putu Piki Pia; Lasmawan, I Wayan; Kertih, I Wayan (Indonesian Values and Character Education Journal, 2024)
Character education in elementary school is an important aspect in forming morale and students' ethics at their stage of development. This study aims to explore the understanding and experiences of pre-service professional teachers in integrating character education with social studies instruction in elementary schools. Employing a mixed-method approach, data were collected through structured questionnaires and in-depth interviews with 124 student teachers enrolled in the teacher education program. The findings indicate that pre-service teachers possess a solid understanding of character education concepts and the importance of their integration into social studies instruction. The researcher implements various strategies such as thematic approaches, project-based learning, and group discussions to instill moral values. However, challenges include time constraints, lack of resources, and insufficient specialized training. The necessary support includes continuous training, access to adequate resources, and mentoring from experienced educators. The study concludes that although pre-service teachers have a strong theoretical understanding, a holistic approach involving training support, resources, and policies is required to enhance the effectiveness of character education integration in social studies instruction. Recommendations for future research include expanding the sample size and employing longitudinal methods for more in-depth and sustained observations.